Preparation of the Cash Budget Based on Activities to Evaluate the Budget - Adheem naeem pachi, Ali Abbas Kareem,; Ali Naeem Jasim, Asaad Gheni Jihad, (Opción, 2019)
This study aims to go into the subject of the preparation of cash budgets in construction companies, according to one of accounting administrative strategy methods through using the basis of activities for the preparation of this budget. The results of the study have signaled to the possibility of application of this technique in the preparation of cash budgets for construction companies. In conclusion, the determination of the optimal cash balance for the contracting company will provide the possibility of identifying the funds to be retained by the contracting companies to meet the withdrawals by it as well as funds.